Development and application of a sampling method for the determination of reactive halogen species in volcanic gas emissions - Rüdiger, Julian; Bobrowski, Nicole (Analytical and bioanalytical chemistry, 2017)
Volcanoes release large amounts of reactive trace gases including sulfur and halogen-containing species into the atmosphere. The knowledge of halogen chemistry in volcanic plumes can deliver information about subsurface processes and is relevant for the understanding of the impact of volcanoes on atmospheric chemistry. In this study, a gas diffusion denuder sampling method using 1,3,5-trimethoxybenzene (1,3,5-TMB)-coated glass tubes for the in situ derivatization of reactive halogen species (RHS) was characterized by a series of laboratory experiments. The coating proved to be applicable to collect selectively gaseous bromine species with oxidation states (OS) of +1 or 0 (such as Br2, BrCl, HOBr, BrO, and BrONO2) while being unreactive to HBr (OS −1). The reaction of 1,3,5-TMB with reactive bromine species forms 1-bromo-2,4,6-TMB—other halogens give corresponding derivatives. Solvent elution of the derivatives followed by analysis with GC-MS results in absolute detection limits of a few nanograms for Br2, Cl2, and I2. In 2015, the technique was applied on volcanic gas plumes at Mt. Etna (Italy) measuring reactive bromine mixing ratios between 0.8 and 7.0 ppbv. Total bromine mixing ratios between 4.7 and 27.5 ppbv were derived from alkaline trap samples, simultaneously taken by a Raschig tube and analyzed with IC and ICP-MS. This leads to the first results of the reactive bromine contribution to total bromine in volcanic emissions, spanning over a range between 12% (±1) and 36% (±2). Our finding is in an agreement with previous model studies, which imply values <44% for plume ages <1 min, which is consistent with the assumed plume age at the sampling sites. Open image in new window Graphical abstract Illustration of the measurement procedure for the determination of reactive halogen species in volcanic plumes.